ZJXG decoction promoted the fracture healing by reducing the decomposition of BMP-7, IGF-1, bFGF and TGFÎ²1 in fracture rats - Zhou, Zhen; Ning, Chi; Wang, Guanxi; Guo, Yunliang; Yang, Guangwen (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The aim is to investigate the effect of Zhuang Jin Xu Gu (ZJXG) decoction on serum levels of bone morphogenetic protein-7 (BMP-7), insulin-like growth factor-1 (IGF-1), basic fibroblast growth factor (bFGF) and transforming growth factor Î²1(TGFÎ²1) and to explore its promoting femoral fracture healing in rats. Femur fractures were generated in 72 male adult Wistar rats by cutting femur transversely at middle point. ZJXG decoction was administered orally after surgery for 28d. The fracture healing process was analyzed by X-ray, gross anatomy and hematoxtlin-eosin (HE) staining. The serum levels of BMP-7, IGF-1, bFGF and TGFÎ²1 were detected by enzyme linked immunobsorbent assay (ELISA). X-ray imaging and gross anatomy indicated that the fibrous callus tissue at the femoral fracture-end increased and the fracture line became fuzzy at 7-14 d following treatment with ZJXG Decoction. HE staining showed that the fibrous-granular tissue at the fracture-end changed gradually to fibrous, cartilaginous and osseous callus tissues from 7d to 28d. ELISA results showed that the serum levels of BMP-7, IGF-1, bFGF and TGFÎ²1 increased significantly 28 days following treatment with ZJXG decoction, compared to model group. It is concluded that ZJXG decoction could enhance the fracture healing by reducing the decomposition of BMP-7 and IGF-1, bFGF and TGFÎ²1 and enhancing their activities.